Μετάφραση και Σχολιασμός των κειμένων: « Iran plays chess, the US plays backgammon», « Saudi Arabia and Iran, not places for persecuted religious and ethnic minorities», «Eastern Mediterranean: a microcosm of regional and global battles» από το blog του James M. Dorsey - (:unkn) unknown (My University, 2021)
Η παρούσα πτυχιακή εργασία εκπονήθηκε στο πλαίσιο των σπουδών μου στο Ιόνιο Πανεπιστήμιο, στη Σχολή Ιστορίας & Μετάφρασης - Διερμηνείας και συγκεκριμένα στο Τμήμα Ξένων Γλωσσών, Μετάφρασης και Διερμηνείας. Σκοπός της είναι μέσα από τη μετάφραση των τριών άρθρων του Τζέιμς Μ. Ντόρσεϊ που παρατίθενται παρακάτω, να αναδειχθεί το μετάφρασμα σε ένα κείμενο, το οποίο να είναι λειτουργικό, προσαρμοσμένο κατάλληλα στη γλωσσική νόρμα του νέου κοινού του, ενώ παράλληλα να έχει παραμείνει πιστό στο πρωτότυπο και τα υφολογικά στοιχεία που το διακατέχουν.

The present undergraduate thesis takes an interest in three articles written by James M. Dorsey. The articles translated have become a reference point for those who wish to engage and take part in the journalist world that includes issues having to deal with Middle East and North Africa. The translation is being accompanied by an analysis, in which the cultural connections, semantic, pragmatic and rhetorical aspects are thoroughly cited.
Keywords: Μετάφραση, Σχολιασμός, Μεταφραστικά Προβλήματα, Μέση Ανατολή; Translation, Commentary, Translation Problems, Middle East